Studi tentang jenis tugas belajar IPA materi ekosistem selama pandemi Covid-19 pada peserta didik kelas V Sekolah Dasar - Masruroh, Aniq; Sukarno, Sukarno; Sriyanto, Muhammad Ismail (Didaktika Dwija Indria, 2023)
Abstract. Case study on types of ecosystem materials of science learning tasks during the COVID-19 pandemic (for class v students at SSDN Pajang 4 surakarta). This research is included in the type of qualitative research with descriptive qualitative methods and case study. The subjects of this study were students, teachers, and parents. Validity testing was used source triangulation and technique triangulation.The results of the study concluded that the type of science learning task on ecosystem materials was observing tasks, namely reading materials to obtain information about ecosystem materials. Communication tasks include reading the food chain and reporting assignments in writing. The task of grouping was to find differences and similarities between symbiosis. This type of predicting task asked students to predict events that will occur if a component changes in the food chain. Constraints encountered by students are student discipline problems when working, facilities constraints, some students still use parental devices, and finally the lack of understanding of ecosystem material. The average student assignment score is 82.5, with 63% getting a score above the KKM. Keywords: Types of assignments, Sciences, Elementary School